2015
DOI: 10.1007/s00216-015-8909-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of species’ blood by attenuated total reflection (ATR) Fourier transform infrared (FT-IR) spectroscopy

Abstract: Blood is one of the most common and informative forms of biological evidence found at a crime scene. A very crucial step in forensic investigations is identifying a blood stain's origin. The standard methods currently employed for analyzing blood are destructive to the sample and time-consuming. In this study, attenuated total reflection (ATR) Fourier transform infrared (FT-IR) spectroscopy is used as a confirmatory, nondestructive, and rapid method for distinction between human and animal (nonhuman) blood. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…In the present study, the PLS model was established based on the calibration dataset and used to predict validation samples. Numerous studies have confirmed the efficiency of this supervised model in classifying or predicting different categories of biological tissues [ 41 , 42 , 14 ]. In Figure 5 A, the PLS score plot illustrates a straightforward separation amongst the four groups, where the control, 12, and 24h groups were distributed along LV1 accounting for 53.72% of total variance, while 24 h and the remaining groups were segregated along LV2 (18.90% of total variation).…”
Section: Resultsmentioning
confidence: 84%
“…In the present study, the PLS model was established based on the calibration dataset and used to predict validation samples. Numerous studies have confirmed the efficiency of this supervised model in classifying or predicting different categories of biological tissues [ 41 , 42 , 14 ]. In Figure 5 A, the PLS score plot illustrates a straightforward separation amongst the four groups, where the control, 12, and 24h groups were distributed along LV1 accounting for 53.72% of total variance, while 24 h and the remaining groups were segregated along LV2 (18.90% of total variation).…”
Section: Resultsmentioning
confidence: 84%
“…In this context, two-dimensional (2D) correlation analysis is commonly used to uncover overlapped bands and discriminate very complex mixtures under the conditions of external perturbations, such as time, temperature, concentration and oxidation 19 23 . Moreover, a combination of FTIR spectroscopy and chemometric methods, including partial least square (PLS) and support vector machine (SVM) models, can convert the characteristic spectral pattern into a classifier or discriminator for automatic classification and prediction among different sample categories 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, ATR-FTIR spectroscopy is rapid, easy to use, and non-destructive—properties that are favourable in forensic practice. Its application in bloodstain identification and species determination has been reported previously 21 , 45 . Nevertheless, to the best of our knowledge, this is the first study demonstrating that ATR-FTIR spectroscopy can be a valuable tool for estimating bloodstain age in mimicked indoor and outdoor crime scenes.…”
Section: Resultsmentioning
confidence: 99%
“… 19 , in which, the aim was to detect early-stage malaria parasites in infected erythrocytes. In the field of forensic science, these two methods have also been used, such as in the identification of species’ blood 20 , 21 and bone 22 , investigation of burned bones 23 , and profiling of cocaine in seizures 24 . In our laboratory, ATR-FTIR in combination with PLSR has proven to be a good tool for the characterization of post-mortem biochemical changes in rabbit plasma 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%